1987
DOI: 10.1017/s0033291700013039
|View full text |Cite
|
Sign up to set email alerts
|

Which boys respond to stimulant medication? A controlled trial of methylphenidate in boys with disruptive behaviour

Abstract: SynopsisThirty-eight boys, referred for psychiatric treatment because of serious problems of behaviour, underwent a double-blind, placebo-controlled, crossover trial of methylphenidate and placebo. Methylphenidate was an effective treatment over a 3-week period. A good response to methylphenidate was predicted by higher levels of inattentive and restless behaviour, impaired performance on tests of attention, clumsiness, younger age and by the absence of symptoms of overt emotional disorder. DSM-III and ICD-9 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
3
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(110 citation statements)
references
References 33 publications
9
96
3
2
Order By: Relevance
“…Few studies have systematically studied multiple predictors of response and these have tended to report contradictory findings. For example, whilst both Taylor et al (1987) and Buitelaar et al (1995) found younger age to be a positive predictor of clinical response to MPH, the study of Taylor observed greater pre-treatment attentional impairment, and hyperactivity, poor performance on attentional tests lower IQ scores, and clumsiness in 'responders'. Buitelaar et al (1995) however, found the opposite pattern of effects with respect to attentional impairment, hyperactivity and IQ, furthermore it was also revealed that responders were more likely than non-responders to have anxiety related difficulties [46].…”
Section: Swanson and Colleagues [Summarised In 13] Investigated The mentioning
confidence: 94%
See 2 more Smart Citations
“…Few studies have systematically studied multiple predictors of response and these have tended to report contradictory findings. For example, whilst both Taylor et al (1987) and Buitelaar et al (1995) found younger age to be a positive predictor of clinical response to MPH, the study of Taylor observed greater pre-treatment attentional impairment, and hyperactivity, poor performance on attentional tests lower IQ scores, and clumsiness in 'responders'. Buitelaar et al (1995) however, found the opposite pattern of effects with respect to attentional impairment, hyperactivity and IQ, furthermore it was also revealed that responders were more likely than non-responders to have anxiety related difficulties [46].…”
Section: Swanson and Colleagues [Summarised In 13] Investigated The mentioning
confidence: 94%
“…However, six studies were identified from the literature that directly examined age as a moderator of stimulant treatment outcome in children and adolescents albeit often across a narrow age range [27, 46, 111, [134][135][136] and one in adults [128]. Whilst the findings from these studies are somewhat inconsistent, this is probably a consequence of the small numbers of participants in many studies and the limited age ranges of some.…”
Section: Is There Any Evidence That Age Is a Moderator Of Stimulant Ementioning
confidence: 99%
See 1 more Smart Citation
“…Parental account of childhood symptom (PACS) is a semi-structured, standardized, investigator-based interview developed as an instrument to provide an objective measure of child behavior. [15][16][17] A trained interviewer administers PACS with parents, who are asked for detailed descriptions of the child's typical behavior in a range of specified situations. Such situations either by external events (for example, watching television, reading a book or comic, playing alone, playing with friends, going to bed, traveling) or by behaviors are shown (for example, crying, worried talk, tempers, fighting with siblings).…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…The following factors have been identified as predicting a positive response to MPH: higher levels of inattentive behaviour (Buitelaar, Van der Gaag, Swaab-Barneveld, & Kuiper, 1995;Taylor et al, 1987;Thomson & Varley, 1998), higher levels of hyperactive behaviour (Barkley, 1976;Thomson & Varley, 1998;Taylor et al, 1987), lower overall severity of the disorder (Buitelaar et al, 1995), poor performance on tests of attention and concentration (Barkley, 1976), younger age (Taylor et al, 1987), high IQ (Buitelaar et al, 1995), presence of a neurological disorder such as seizures (Thomson & Varley, 1998), positive parent cognitions (Hoza et al, 2000), being male (Handen, Janosky, McAuliffe, Breaux, & Feldman, 1994), higher socio-economic status (Handen et al, 1994), and having the 10-repeat DAT1 allele (Kirley et al, 2003). Thus, poor performance on some cognitive tasks (mainly measuring attention and concentration) has been identified as a predictor, but to our knowledge nobody has studied whether performance on a response inhibition task predicts MPH response.…”
Section: Speed Of Inhibition Predicts Teacher-rated Medication Responmentioning
confidence: 99%